The correspondence model of cross-cultural adjustment: exploring exchange relationships - Haslberger, Arno; Dickmann, Michael (Emerald, 2016)
Purpose There has been tremendous interest in the field of cultural adjustment in the past decades. The work of Black and his colleagues has inspired many researchers. However, critics have pointed out that their original conceptualization has limitations; most of the insights building on their model have probably been harvested. Therefore, it is appropriate to investigate alternative ways at understanding the challenges in international assignments. In this paper we outline a model rooted in person-environment (P-E) fit theory. We follow Dawis and Lofquist’s Theory of Work Adjustment (TWA), which has had only a small influence on expatriate research to date. - Design/methodology/approach The paper develops a correspondence model of cross-cultural adjustment and explores the diverse factors and their interactions in-depth. The satisfaction of individual needs and corresponding environmental supplies (macro, micro and organizational factors) as well as the satisfactoriness of individual abilities and corresponding environmental requirements (macro, micro and organizational) is outlined. - Findings Based on the literature and the model a large number of hypotheses in relation to cross-cultural adjustment are proposed which allow new avenues in adjustment research. - Originality/value The contribution of this paper is to propose a model that addresses the main criticisms to the adjustment conceptualization of Black and his colleagues.